Multimodal pattern recognition of social signals in human-computer-interaction : third IAPR TC3 Workshop, MPRSS 2014, Stockholm, Sweden, August 24, 2014, Revised selected papers /: third IAPR TC3 Workshop, MPRSS 2014, Stockholm, Sweden, August 24, 2014, Revised selected papers. (2015) - Unknown
No abstract available